Room temperature CO2 reduction to solid carbon species on liquid metals featuring atomically thin ceria interfaces - Dorna Esrafilzadeh (Nature Portfolio, 2019)
While CO2 reduction proves an appealing means to convert greenhouse emissions to high-value products, there are few materials capable of such a conversion. Here, the authors demonstrate a liquid-metal electrocatalyst to convert CO2 directly into solid carbon that can be used as capacitor electrodes.